2015
DOI: 10.1038/nrneph.2015.208
|View full text |Cite
|
Sign up to set email alerts
|

The mucosa–kidney axis in IgA nephropathy

Abstract: Links between IgA nephropathy (IgAN) and the mucosa have been recognized since the 1970s. In particular, the observation of visible haematuria induced by respiratory infections in patients with IgAN and the association of IgAN with diseases in which the mucosa plays a part, especially coeliac disease, have been taken as evidence of a mucosa-kidney axis. Here, we review current evidence that links the mucosa, in particular the gastrointestinal mucosa, and IgA produced by the bone marrow with IgAN. Genome-wide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 83 publications
1
90
0
2
Order By: Relevance
“…Some researchers have suggested a new hypothesis for the intestine – kidney connection when considering the possible mechanism for the pathogenesis of IgAN [31, 32]. Because C. rectus and S. mutans are oral bacterial species, our data provide evidence for a new concept of an oral – kidney association.…”
Section: Discussionsupporting
confidence: 56%
“…Some researchers have suggested a new hypothesis for the intestine – kidney connection when considering the possible mechanism for the pathogenesis of IgAN [31, 32]. Because C. rectus and S. mutans are oral bacterial species, our data provide evidence for a new concept of an oral – kidney association.…”
Section: Discussionsupporting
confidence: 56%
“…The synthesis and binding of antibodies directed against Gd-IgA1 lead to the formation of pathogenic IgA1-containing immune complexes, which activate mesangial cells, inducing the proliferation and expansion of the extracellular matrix and the production of cytokines and chemokines and activating the complement system through the alternative or lectin pathway, resulting in renal injury [13]. Additionally, mucosa-kidney axis disorders have been speculated to be involved in the pathogenesis of IgAN [8]. In a mouse model of IgAN, an association was observed between TLR9 polymorphisms and disease progression [14].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of HCQ may result from its ability to inhibit the activation of toll-like receptors (TLRs) and numerous cytokines [7], which are also crucial in the abnormal mucosa-kidney axis in IgAN [8]. Gao et al [9] found that HCQ reduced proteinuria to 65.9 ± 25.5% ( p = 0.002) of the baseline level (0.90 ± 0.45 g/day) in patients with IgAN; however, there was no statistically significant difference in proteinuria levels between the HCQ and losartan groups.…”
Section: Introductionmentioning
confidence: 99%
“…The classical clinical picture in IgAN of recurrent episodes of visible hematuria coinciding with upper respiratory or intestinal tract infections indicate that mucosal immunity plays an important role in the pathogenesis of IgAN [18] . IgA1 is secreted by antibody-secreting B cells in distinct mucosal and systemic compartments with a characteristic site-specific phenotype [19] .…”
Section: Regulation Of Iga Class Switch Recombination Inmentioning
confidence: 99%